2009
DOI: 10.1155/2010/281913
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter Substructure and Dwarf Galactic Satellites

Abstract: A decade ago cosmological simulations of increasingly higher resolution were used to demonstrate that virialized regions of Cold Dark Matter (CDM) halos are filled with a multitude of dense, gravitationally-bound clumps. These dark matter subhalos are central regions of halos that survived strong gravitational tidal forces and dynamical friction during the hierarchical sequence of merging and accretion via which the CDM halos form. Comparisons with observations revealed that there is a glaring discrepancy betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(181 citation statements)
references
References 233 publications
(311 reference statements)
5
176
0
Order By: Relevance
“…In this case, planting galaxies following the host halo profile is the correct choice. Such a selection effect has already been noted by Nagai & Kravtsov (2005) and Kravtsov (2010). Conroy, Wechsler & Kravtsov (2006) and Chen et al (2006) showed that populating subhaloes according to their infall properties provides a better match to the observed spatial distribution or clustering of galaxies, although they only studied surviving subhaloes (i.e.…”
Section: Do Galaxies Trace Subhaloes?mentioning
confidence: 69%
“…In this case, planting galaxies following the host halo profile is the correct choice. Such a selection effect has already been noted by Nagai & Kravtsov (2005) and Kravtsov (2010). Conroy, Wechsler & Kravtsov (2006) and Chen et al (2006) showed that populating subhaloes according to their infall properties provides a better match to the observed spatial distribution or clustering of galaxies, although they only studied surviving subhaloes (i.e.…”
Section: Do Galaxies Trace Subhaloes?mentioning
confidence: 69%
“…Moore et al (1999) argue that the number of dark matter subhalos is 10 − 100 times larger than the number of satellites observed around the Milky Way (Kravtsov 2010). The so-called "missing satellite problem" has been revisited in a somewhat quantitative context (Boylan-Kolchin et al 2011;Lovell et al 2012;Boylan-Kolchin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Including that in cosmological models seems to be one way forward to understanding the evolution of galaxies over cosmic time (Kravtsov 2010). Varying global efficiency of star formation is a natural consequence of gravitational instability in galaxies with varying properties.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than H 2 formation being the gate to star formation, perhaps large scale gravitational collapse leads to both H 2 formation, and, not much later, to star formation. Indeed, simulations of H 2 formation in a self-gravitating, magnetized, periodic, turbulent box show that (Glover & Mac Low 2007, 2010) the density enhancements produced by supersonic turbulence can lead to substantial molecular fractions within a few million years. The fraction of molecular hydrogen in these simulations shows a clear dependence on the density of the gas in the box.…”
Section: Midplane Pressurementioning
confidence: 99%